PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP SEMANGAT KERJA PADA VILYA COMPUTER KARANGASEM - Sujana, I Made; Suandi, I Nyoman; Astra, I Gede Rentawan Wana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
Leaders must also be able to provide encouragement and motivate employees to work well in order to achieve goals desired by the company. Leadership and motivation have an immediate effect on employee morale. Referring to the fact that researchers interested in conducting research on